Memposisikan Konsep Mahram Dalam Konteks Kehidupan Kekinian - Jailani, Imam Amrusi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
The concept of mahram relates to a number of issues, such as marriage, casual relationship, the disclosure of male and female aurat, as well as women's travelling. While the discussion of mahram which relates to the first three issues does not create contradiction, the injunction of mahram with women's travelling is stimulating long lasting debates in our present time. For instance with the case of Muslim women going to the holy land to perform hajj; the government does not permit women to perform hajj without accompied by their mahram. In reality however, for those women who have no mahram, the government will find them 'fake mah ram' so that they can go to hajj. In this case, what does mahram mean, what is the purpose of mah ram?